Early sexual initiation in a group of juvenile mothers - Łepecka-Klusek, Celina; Bałanda-Bałdyga, Agnieszka; Stadnicka, Grażyna; Marczak, Edyta (Polish Journal of Public Health, 2012)
Introduction. Not only in Poland, has the age of sexual initiation decreased significantly over the past few decades. Aim. The aim of this study is to verify what the determinants of early sexual initiation among contemporary juvenile mothers are. Material and methods. The study involved 73 mothers who gave birth before the age of 19. A questionnaire specially designed for the purpose of the study was applied as a research tool. The preparation stage of research tool was concluded by a pilot study attended by 11 young mothers. Then, the collected material was subjected to descriptive and statistical analysis. Results. The examined group was diverse in age, place of residence and family structure. More than half of respondents (39, 53.4%) started intercourse at the age of 15-16, 27 mothers (37.0%) of them at the age of 17-18 and the remaining seven respondents (9.6%) at the age of 13-14. The use of conception control methods, most often condoms, during their first intercourse was reported by 58 mothers (79.4%) . Half of them described their knowledge on human sexuality and family planning as insufficient for their needs. Conclusions. The age of juvenile mothers at delivery, their place of residence and family structure are significantly related to the age of sexual initiation. The teenagers’ knowledge on human sexuality and family planning comes largely from the media and peers, which may be related to the development of risky sexual behaviour.